Badanie poziomu rozwoju powiatów północno-zachodniego regionu Polski w latach 1999-2002 - Rozkrut, Monika; Rozkrut, Dominik (Analysis of the Relative Development of Districts of the North-Western Province of Poland in the Period of 1999-2003, 2005)
We study the level of development of districts in north-western region of Poland. This is one of the six regions established in Poland according to The Nomenclature of Territorial Units for Statistics (NUTS). Major socio-economic regions (NUTS 1) are used for analyzing regional Community problems and for the purposes of appraisal of eligibility for aid from the Structural Funds. In 2004 governmental commission decided how to divide Poland into six NUTS 1 regions. The regions were formed as groups of voivodships. After that, authorities from voivodeships whose development was lagging behind, expressed their concerns about being joined with wealthier voivodships in one region, what statistically improves their socio-economic situation (and reduces expected flows of structural funds). In the paper we tried to verify these concerns. The objects of the study were districts of north-western region. We evaluated the level of economic development and its spatial diversification, using synthetic taxonomic measure of development, tree clustering and k-means clustering.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 593-604